2012
DOI: 10.1179/1476830512y.0000000002
|View full text |Cite
|
Sign up to set email alerts
|

Plasma magnesium levels and treatment outcome in depressed patients

Abstract: Although further studies investigating the relationship between hypomagnesaemia, depression, and treatment outcome are certainly necessary, we have hypothesized that hypomagnesaemia could be an epiphenomenic biochemical trait in less drug-responsive depressed patients. It is also plausible that lower Mg levels and hyperactive traits identify a biological subtype of patients with increased catecholaminergic functioning and a poorer response to aminergic drugs. Moreover, Mg depletion could partly account for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 33 publications
0
24
1
1
Order By: Relevance
“…In contrast to our findings Camardese et al reported low plasma Mg 2þ levels to be predictive for worse response to standard antidepressant treatment (Camardese et al, 2012). Patients in their study were off antidepressant medication for at least 1 week and not hospitalized, i.e.…”
Section: Discussioncontrasting
confidence: 85%
“…In contrast to our findings Camardese et al reported low plasma Mg 2þ levels to be predictive for worse response to standard antidepressant treatment (Camardese et al, 2012). Patients in their study were off antidepressant medication for at least 1 week and not hospitalized, i.e.…”
Section: Discussioncontrasting
confidence: 85%
“…Since the mechanism of magnesium’s role in depression is still not clear, it is difficult to say why this relationship with antidepressants may exist. In a sample of treatment resistant depressed patients with normal magnesium levels, those with high normal magnesium levels had a more robust response to antidepressants [29]. In another study, severity of depression correlated with reduced intracellular magnesium, and that cellular levels normalized after successful treatment with antidepressants [30].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important prevention-related aspects is the influence of nutritional factors. It has been proved that Mg deficiency may play an important role in the development of depression and mood disorders [8–10]. …”
Section: Introductionmentioning
confidence: 99%